967 Evaluating temperature changes and volatile organic compound off-gassing in turnout protective gear ensembles among florida firefighters. (24th April 2018) - Santiago, Katerina M; Caban-Martinez, Alberto J; Baum, Jeramy; Pangborn, Johnathan; Dikici, Emre; Solle, Natasha Shaefer; Sterling, David; Koru-Sengul, Tualy; Moore, Kevin; Salvaterra, Isabelle; Daunert, Sylvia; Deo, Sapna; et al.
Abstract : Introduction: Firefighter protective gear ensembles have been shown in controlled laboratory and staged live fire training experiments, to collect and harbour carcinogens such as polycyclic aromatic hydrocarbons (PAHs) and volatile organic compounds (VOCs). Protective gear is often time transported in the personal vehicle of firefighters, resulting in cross-contamination between the vehicle and the fire incident environment. In the Southern United States particularly, ambient warmer temperatures may influence the rate of VOC gear off-gassing. This pilot study characterises temperature and particle off-gassing of firefighter turnout gear immediately following a 24 hour work shift. Methods: Twelve sets of gear were obtained from South Florida career firefighters. Their protective gear, including helmet, gloves, hood, pants, boots and turnout coat, were placed in a large vacuum sealed Pelican case immediately after a 24 hour work shift. Turn-out gear was randomly selected at each fire station regardless of fire exposure. A photoionization gas detector (0.2 to 200 ppm), MetOne particle counter, Chromosorb diffusion patch, and a temperature logger were placed in each case with the ensemble for a 24 hour collection period. Results: In two extreme observation points, VOC off-gassing was moderately, but significantly, correlated with temperature changes within the exposed gear (case#1: r=0.50; p<0.001) while a low correlation was observed in case#2 (r=0.06; p=0.01). Fine particulate matter (1–10 µm) was documented at least up to 1 hour after the gear was placed in most cases. Smaller size (0.3–0.5 µm) particulate matter was present up to 5 hours after placement across several cases. Discussion: Firefighter turnout gear used during real-life fire incident response events was documented to release VOCs and particles immediately after a 24 hour work shift. These results suggest the importance of the development of robust decontamination procedures immediately following a fire incident response is needed to reduce exposure to potential carcinogens from firefighter protective gear.